Are There Barriers for Professional Development of Women Dentists? A Qualitative Study in Saudi Arabia. (April 2017) - Rajeh, M.; Nicolau, B.; Pluye, P.; Qutob, A.; Esfandiari, S.
Globally, there is an upward trend in the number of women applying to dental schools and entering the profession of dentistry. Women dentists aim to advance their careers; however, differences exist between men and women dentists regarding leadership positions and work titles. For example, in Saudi Arabia, women usually occupy lower ranked positions than men in the Saudi public sector, and they are, therefore, paid less than their male counterparts. This study aimed to explore the possible barriers to Saudi women dentists' professional advancement using a qualitative descriptive study design. Specifically, semistructured in-depth interviews were conducted with 13 women practicing dentistry in the Makkah region of Saudi Arabia. The interviews were audio-recorded and transcribed verbatim, and the data were interpreted using qualitative content analysis (NVivo 11; QRS International). The results revealed 4 challenges that might delay the participants' career development. These include family-related challenges, sociocultural challenges, workplace challenges, and transportation issues. From this perspective, some perceived barriers to the professional development of women dentists were found that might not be unique to Saudi Arabia, and the article's suggestions and recommendations aim to minimize the effects of these barriers impeding women's advancement in dentistry in Saudi Arabia. Knowledge Transfer Statement: This study makes an important contribution to knowledge on this topic. These results will aid policy makers' efforts to create supportive work environments through gender-specific incentives that meet the current professional and family needs of women dentists, particularly those in Saudi Arabia.